Personality Traits of High School Students in Makassar - Basti, Basti; Dewi, Eva Meizara Puspita; Agussalim, Amirah Aminanty; Rasyid, Nurfajriyanti (Indonesian Journal of Educational Studies, 2022)
Abstract. The sample in this study were 404 students, consisting of 116 boys (28.7%) and 288 girls (71.3%). The students involved in this study were aged between 15 and 18 years (M = 16.6; SD = 0.741), and the majority were from the Bugis ethnic group (76.5%). The selection of the sample in this study is related to the research objective, which is to focus on adolescents (high school students), so that the age range taken represents adolescence, using a multistage cluster random sampling technique. The measuring instrument used in this study is the Big-Five Inventory (BFI) which has been adapted by Ramdhani (2012). This scale consists of 44 statement items which are divided into five personality traits, namely extraversion (8 items), agreeableness (9 items), conscientiousness (9 items), neuroticism (8 items), and openness (10 items). Data analysis used in this research is descriptive and inferential analysis (Anova and crosstabulation). The results of this study indicate that there are 119 (29.5%) students showing a tendency of neuroticism, there are 64 (15.8%) students showing an openness tendency, there are 70 (17.3%) students showing a tendency to agreeableness, there are 69 (17.1%) %) students showed a tendency of extraversion, and there were 82 (20.3%) students showing a tendency of conscientiousness.